ROLE OF ETHICS AND MORAL EDUCATION - DR. ANITA (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Individuals will accept external moral authority when it is independently filtered. The problem is that most public service leaders do not follow a consistent approach to ethical decision making and accomplishing ethical behavior in the bureaucratic organizations they lead. While formal codes of ethics offer some standards of conduct and guidelines for ethical decision-making, a more effective approach is to mesh code enforcement with a normative approach to establishing an ethical climate. Public Administrative style, methods, hierarchy and training are closely interrelated with ethics. Training alone is not enough. However, serious, sustainable improvements of the public service without adequate education and training seem to be impossible. Evaluation of training policies in every country in the region appears to be necessary. Public servants must understand what is acceptable behavior, and, in the end, when the risk of detection and punishment outweighs the gains. Modern people who have embraced scientific development as truth do not judge goodness according to the will of God. They ask their own insight for advice and often end up in conflict because insights differ. If we concentrate on the basis of the conflict, we discover common ground that is often hidden or misconstrued.